Experimental analysis of anisotropic damage in dual-phase steel by resonance measurement. (November 2017) - Gerstein, Gregory; Clausmeyer, Till; Isik, Kerim; Nürnberger, Florian; Tekkaya, A Erman; Bruchanov, Arkadii A; Maier, Hans J
The ductile damage in deformed dual-phase steel sheets (DP600) was investigated based on measurements of the degradation of the direction-dependent Young's modulus. The study focuses on the material-induced damage anisotropy in such advanced high-strength steel. The elastic properties in the direction of applied loading of the deformed sheets were determined by measuring the resonance frequency of rectangular samples. The material was investigated in the as-delivered condition and after annealing at 220℃ for 48 h. Tensile strains of up to 10% were applied after annealing. Tensile tests were performed in different directions with respect to the rolling direction to determine the evolution of damage in different directions. The comparison of the obtained results with the electron micrographs shows that the damage in the steel sheets occurs in the form of nano and micro damages near the grain boundary and interfaces of phases. The maximum decrease of the Young's modulus in the transverse direction was observed for the largest applied deformation of 10% tensile strain in the transverse direction. An efficient calculation method to obtain information on the distribution of anisotropy in the plane of the sheet was applied. This calculation method relies on an efficient representation of the material's texture. In order to assess the influence of texture, the texture was determined experimentally.